2009
DOI: 10.1099/vir.0.016378-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecies diversity of SARS-like coronaviruses in Rhinolophus sinicus and its implications for the origin of SARS coronaviruses in humans

Abstract: The Chinese rufous horseshoe bat (Rhinolophus sinicus) has been suggested to carry the direct ancestor of severe acute respiratory syndrome (SARS) coronavirus (SCoV), and the diversity of SARS-like CoVs (SLCoV) within this Rhinolophus species is therefore worth investigating. Here, we demonstrate the remarkable diversity of SLCoVs in R. sinicus and identify a strain with the same pattern of phylogenetic incongruence (i.e. an indication of recombination) as reported previously in another SLCoV strain. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 16 publications
5
86
1
Order By: Relevance
“…The major bat species in the site where Bat CoV B15‐21 was collected was Rhinolophus ferrumequinum , which is consistent with a previous report that SARS‐CoV‐like bat CoVs were mostly found in Rhinolophus spp. (Yuan et al., ). The amino acids of its full spike gene showed that the B15‐21 strain is closely related to SARS‐CoV‐like Bat CoVs Rp3, Rf1, HKU3‐2 and 273 rather than human SARS‐CoVs and Bat CoV RaSHC014, which was reported to have high potential for human emergence (Menachery et al., ) and showed two specific deletion sites in the RBD of the spike protein.…”
Section: Discussionmentioning
confidence: 99%
“…The major bat species in the site where Bat CoV B15‐21 was collected was Rhinolophus ferrumequinum , which is consistent with a previous report that SARS‐CoV‐like bat CoVs were mostly found in Rhinolophus spp. (Yuan et al., ). The amino acids of its full spike gene showed that the B15‐21 strain is closely related to SARS‐CoV‐like Bat CoVs Rp3, Rf1, HKU3‐2 and 273 rather than human SARS‐CoVs and Bat CoV RaSHC014, which was reported to have high potential for human emergence (Menachery et al., ) and showed two specific deletion sites in the RBD of the spike protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all rhinolophid bat species have been tested for SARS-related coronaviruses. For example, only 12 of the at least 19 rhinolophid bat species that occur in China have been tested and SARS-related coronavirus sequence information is only available from 5 of these species Li et al, 2005;Poon et al, 2005;Tang et al, 2006;Woo et al, 2006Woo et al, , 2007Yang et al, 2013;Yuan et al, 2010). Therefore, further studies of Rhinolophus species in Africa, Europe and Asia may provide more insight into the ancestral bat viruses that were the source of the emergence of human SARS-CoV.…”
Section: Evidence For Phylogenetic Co-segregation Of Coronaviruses Anmentioning
confidence: 99%
“…The prototype strains of this feline virus are recombinants between FIPV type 1 and CCoV in different parts of the ORF1b and Spike genes (Herrewegh et al, 1998). Recombination has also been hypothesized to be involved in the emergence of the SARS-CoV Hon et al, 2008;Lau et al, 2010a;Yuan et al, 2010) and HCoV-OC43 genotypes (Lau et al, 2011). However, the observed recombination events in SARS-CoV and HCoV-OC43 are restricted to genetically closely related viruses.…”
Section: Mechanisms Of Host Switchesmentioning
confidence: 99%
“…Wildlife is believed to be responsible for approximately 40% of the emerging infectious diseases in humans (Quan et al, 2013). Among them, bats have been found to be natural reservoirs for many important zoonotic viruses, such as the Marburg virus (Towner et al, 2009), Ebola virus (Leroy et al, 2005), Hendra virus (Chan and Chan, 2013) and severe acute respiratory syndrome (SARS) coronavirus (2003) (Lau et al, 2005;Yuan et al, 2010). A series of characteristics have supported bats as a suitable reservoir host for viruses, including their long lifespan, high species diversity, unique immune systems, gregarious roosting behaviors, and high spatial mobility and population densities (Calisher et al, 2006).…”
Section: Introductionmentioning
confidence: 99%